Computational fluid dynamic modeling of pressure and velocity in a water aspirator - Krzysztof Tadyszak; Mariia Rabyk; Jiří Pánek; Martin Hrubý (Heliyon)
This study presents the experimental and theoretical modeling results of pressure changes caused by fluid flow in a water aspirator (water pump) whose working principle is based on the Venturi effect. Experimentally measured pressure drop in a glass-made device is modeled in COMSOL Multiphysics by previously reproducing the device geometry. Computations were performed using a Fluid Flow Module with turbulence model RANS k-ε. Pressure and liquid velocity magnitude maps were drowned, and selected vertical and perpendicular cross-sections of velocity and pressure fields were shown and discussed, indicating model limitations.